THE USE OF FOREIGN LANGUAGES ​​IN EMPLOYMENT AGREEMENTS WITH FOREIGN WORKERS: A LEGAL ANALYSIS BASED ON SUPREME COURT DECISION NUMBER 51 K/PDT.SUS-PHI/2025 FROM THE PERSPECTIVE OF INTERNATIONAL CONTRACT LAW - Ainun Nabilah; Rouli Anita Valentina (Catalist Indo Publisher, 2026)
This study examines the use of foreign languages in employment agreements involving foreign workers in Indonesia based on Supreme Court Decision No. 51 K/Pdt.Sus-PHI/2025 and analyzes its application from the perspective of international contract law through a normative juridical method. By reviewing Article 31 of Law No. 24 of 2009, which mandates the use of the Indonesian language in contracts involving national parties, the research finds that foreign-language contracts remain permissible as long as they do not compromise mutual understanding or the equality of the parties. The Supreme Court decision affirms that a contract drafted in a foreign language is not automatically null and void but must comply with principles of legal certainty, worker protection, and national mandatory rules. A bilingual contract emerges as an ideal mechanism to balance the practical needs of international employment relations with national legal obligations. This study concludes that harmonizing domestic regulations with international contracting practices is essential to ensuring legal certainty and fairness in employment relationships involving foreign workers in the era of globalization.